Molecular design enabled reduction of interface trap density affords highly efficient and stable perovskite solar cells with over 83% fill factor. (October 2018) - Meng, Xiangyue; Ho, Carr Hoi Yi; Xiao, Shuang; Bai, Yang; Zhang, Teng; Hu, Chen; Lin, He; Yang, Yinglong; So, Shu Kong; Yang, Shihe
Abstract: Advancing perovskite solar cell (PVSC) technologies toward its theoretical power conversion efficiency (PCE) and optimum stability requires stringent control over interfacial trap densities in the devices. By introducing a new macromolecular interlayer material of PPDIN6 at the PCBM/Ag interface for planar p-i-n PVSCs, we succeeded in significantly reducing the trap density, thereby facilitating electron extraction and suppressing electron recombination at the interface. Consequently, a PCE of 20.43% was achieved with a record fill factor of 83.4%, which is one of the highest values for planar p-i-n PVSCs. Moreover, the amine groups in PPDIN6 could neutralize the migrating iodide ions and thus inhibit the formation of the insulating Ag–I bonds on the surface of the Ag electrode. As a result, we realized long-term stability for PPDIN6 based PVSCs, which maintained 85% of their initial performance after continuous operation at their maximum power point for 200 h under 1-sun illumination in air with a relative humidity of 30–50%. Graphical abstract: fx1 Highlights: Design and synthesize a new macromolecular interlayer material of PPDIN6 at the PCBM/Ag interface for planar p-i-n PVSCs. Lower trap density in the PPDIN6 based PVSC device by performing temperature dependent admittance spectroscopy. High PCE with an over 83% fill factor was achieved with high device stability.